On the comparative morphology of the juvenile avian skull: An assessment of squamosal shape across avian higher‐level taxa. Issue 4 (9th September 2020) - Mayr, Gerald; Manegold, Albrecht
Abstract: The comparative morphology of juvenile avian skulls is poorly known. Here, we survey the shape of the squamosal (os squamosum) across juvenile skulls of avian higher‐level clades. In all palaeognathous birds, the rostral end of the squamosal does not surpass the parietal and does not reach the frontal. This morphology is likely to be plesiomorphic for neornithine birds. A short squamosal also occurs in some Neognathae, but in most neognathous birds the squamosal contacts the frontal, and in some taxa the bone is strongly elongated and distinctly surpasses the parietal. Some clades show a notable variation in squamosal morphology. This is, for example, true for Strigiformes, where the taxon Athene differs from the other examined owls in squamosal size, and for the Passeriformes, where Old World Suboscines are characterized by a distinctive squamosal morphology. A unique derived squamosal morphology is for the first time reported for the Apodidae and Hemiprocnidae, in which the bone forms a elongated rostral process that runs along most of the orbital rim. In non‐avian theropods, the squamosal articulates with the postorbital and delimits the upper temporal opening. Extant birds lack a postorbital, but a topological correlation between the squamosal and the postorbital process is maintained in most taxa of the Neognathae. The phylogenetic significance of squamosal morphology is diminished by the fact that closely related taxa often show very disparate shapes of the bone, and squamosal morphology appears to be determined by multiple functional constraints including skull geometry, brain morphology and, possibly, nostril type.